Peran Tokoh Agama Dalam Penanganan Pandemi Covid-19 di Kota Malang - Siti Kholifah; Siti Zurinani (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
At the moment, religion study is an important issue in the study of epidemiology. WHO also has issued practical recommendations for religious leaders and faith-based communities to take part in handling the Covid-19 pandemic. Referring this recommendation, this research focuses the role of religious leaders in handling the Covid-19 pandemic in Malang City. This study is considered very important, because in Indonesia, the government is still not able to optimize the role of religious leaders in handling the pandemic. As a result, in many violations of health protocols initiated by religious activities. This study uses a qualitative method and an explanatory case study approach, using Putnam and Coleman’s social capital theory. This research show that religious leaders who understand this pandemic as a process of social change that will occur in life and are an epidemic of disease, they have sigsinificant role in minimizing the spread of Covid-19 by limiting religious activities, and urging their followers to obey on helath protocols and carry out vaccinations. Religious leaders are using their social capital in dealing with this pandemic. This creates bonding within the internal religious community, and creates bridging with other institutions in the religious community. In addition, there is a link between the network of religious leaders and the government that is useful in handling the pandemic. However, there are also religious leaders who do not believe in the existence of Covid-19, and tend to act controversial activities with policies to handle the pandemic. This condition causes the bonding among the people is unadequate because the people are devided. Moreover, bridging and linking are also unadequated, because religious leaders tend to be closed to the government and community leaders who will provide socialization abot Covid-19.